2013
DOI: 10.1097/fjc.0b013e318290922f
|View full text |Cite
|
Sign up to set email alerts
|

Factor IX Complex for the Treatment of Severe Bleeding After Cardiac Surgery

Abstract: In this small group of patients, Factor IX Complex effectively controlled severe bleeding after cardiac surgery preventing the need for re-exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies were observational studies (n=49), 16 studies were RCTs, and 3 were meta‐analyses (Tables 1 and 2). 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 Of the 16 RCTs identified,1...…”
Section: Resultsmentioning
confidence: 99%
“…Factor IX A retrospective study of 11 patients receiving 35 mg kg À1 versus controls showed that factor IX produced a significant reduction in chest tube drainage, but it had no significant effect on blood product usage. 233…”
Section: Antithrombinmentioning
confidence: 99%
“…A recent study has shown factor IX to be effective in reducing blood loss following CPB although this was in a small number of patients ( n = 11) and reduction of blood product usage was not statistically significant. The authors also reported three adverse incidents including pulmonary embolus and acute renal failure (Clark et al , ).…”
Section: Additional Treatmentsmentioning
confidence: 99%